Baobab Tree - Ghosh, Ayan (2023)
The Agri Horticultural Society had first started a botanical garden at Sewri, but it didn't catch on. The garden became popular after the site shifted to Byculla. The garden started as a repository of exotic plants, herbs and trees, which the British had collected from Africa, Australia, New Zealand, Madagascar, China, Sri Lanka, India and other British colonies.